Use of a reabsorbable patch as tracheal substitute in a complicated urgent tracheostomy. (4th October 2020) - Mammana, Marco; Comacchio, Giovanni M; Bellini, Alice; Rea, Federico
Abstract: Airway dehiscence after tracheal resection-anastomosis is a major complication that often requires an urgent reoperation. If ischaemia of the airway is extensive, however, performing a tracheostomy might be complicated. Here, we describe the case of a patient who underwent urgent tracheostomy because of acute airway dehiscence, wherein an absorbable prosthesis was used to repair the defect of the anterior trachea. Abstract : Tracheal resection-anastomosis is the treatment of choice for benign airway stenosis; however, severe anastomotic dehiscence may occur.